HUBUNGAN INDEKS MASSA TUBUH TERHADAP SKALA SESAK NAPAS PADA PENDERITA PENYAKIT PARU OBSTRUKTIF KRONIS STABIL PRIA - Zulkarnain Zulkarnain; A P Tarigan (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2019)
COPD is an obstructive pulmonary disease that impact significantly in patients’ quality of life. Dyspnea as a main complaint in COPD patients often occur when the patients do simple thing in their daily life. There are few factors contribute to this condition. From few studies, cachexia as late manifestation of COPD often associated with worse manifestation of dyspnea. The aim of this study is to know whether there was a correlation between body mass index (BMI) and dyspnea scale in COPD patients. This is an analytical study with cross sectional design that involved 34 male participants with diagnosis of COPD. Body mass index was measured by Bioelectrical Impedance Analysis (BIA) and Borg scale was used to measure the dyspnea scale. Spearman Test was used to analyze the correlation between BMI and dyspnea scale. In this study, the majority of patients were obesity (44.1%), but it had slight difference from underweight state (41.2%). Median of BORG scale was 3.0 with range 1-7. From analysis, there was no significant correlation between BMI and dyspnea scale with p-value > 0.05. So, it was concluded that there was no significant correlation between BMI and dyspnea scale in COPD patients. It might be because of few confounding factor that can contribute to this condition.